Analisis Asesmen Keterampilan Berpikir Kritis Siswa Melalui Ulangan Harian Mata Pelajaran Fiqh Di Madrasah Aliyah - M. Yemmardotillah; Rini Indriani; Elvi Rahmi; Pismawenzi Pismawenzi (An-Nuha, 2026)
This study aims to analyze the assessment of students’ critical thinking skills through daily tests in the Fiqh subject at MAN 3 Padang Panjang. It employs a descriptive qualitative approach to examine assessment forms and students’ critical thinking as reflected in test results. The subjects include Fiqh teachers and students, while the object is the assessment of critical thinking through daily tests. Data were collected through document analysis of test items and student responses, teacher interviews, and supporting observations. Data analysis followed the Miles and Huberman model, with validity ensured through source and technique triangulation. The findings show that daily tests include elements of critical thinking through essay and contextual case-based questions, but are not yet systematically designed based on comprehensive indicators. Students’ critical thinking skills are at a moderate level, dominated by basic analytical abilities. The study highlights the importance of strengthening HOTS-oriented assessment in Fiqh learning.